2021
DOI: 10.1101/2021.09.07.459322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Illuminating links between cis-regulators and trans-acting variants in the human prefrontal cortex

Abstract: Psychiatric disorders exact immense human and economic tolls in societies globally. Underlying many of these disorders is a complex repertoire of genomic variants that influence the expression of genes involved in pathways and processes in the brain. Identifying such variants and their associated brain functions is thus essential for understanding the molecular underpinnings of psychiatric disorders. Genome-wide association studies (GWASes) have provided many variants associated with these disorders; however, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In previous work, SRRM2 has been shown to play a role in the tauopathy of Alzheimer's disease [36][37][38] , and de novo mutations in this gene have been linked to developmental disorders 39 . AKAP11 was suggested as a trans-gene linking to a SCZ GWAS signal in a recent study 40 , which considered together with our results, adds to examples of convergence of common and rare variant associations on the same gene. A recent metaanalysis of SCHEMA and a bipolar disorder (BD) dataset also found exome-wide significance for AKAP11 41 , suggesting a role of this gene in the shared etiology of SCZ and BD.…”
Section: Mainsupporting
confidence: 77%
“…In previous work, SRRM2 has been shown to play a role in the tauopathy of Alzheimer's disease [36][37][38] , and de novo mutations in this gene have been linked to developmental disorders 39 . AKAP11 was suggested as a trans-gene linking to a SCZ GWAS signal in a recent study 40 , which considered together with our results, adds to examples of convergence of common and rare variant associations on the same gene. A recent metaanalysis of SCHEMA and a bipolar disorder (BD) dataset also found exome-wide significance for AKAP11 41 , suggesting a role of this gene in the shared etiology of SCZ and BD.…”
Section: Mainsupporting
confidence: 77%
“…Colocalization analysis has been implemented to evaluate whether GWAS and eQTLs are explained by a shared set of variants. To test how many IDE variants are also identified from the colocalization analysis, we compared IDE variants with colocalization between schizophrenia GWAS and adult brain eQTLs (Liu et al, 2021) using the coloc package ( Methods ). Because colocalization does not always indicate a specific variant, we tested how often eGenes (genes detected as having an associated eQTL) linked to IDE variants were also observed from colocalization analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Intersection of MPRA and eQTLs also pruned the gene list ( Figure 3B ). We initially detected 288 eGenes to be associated with schizophrenia by colocalization analysis, covering 78 loci (Liu et al, 2021). An orthogonal analysis of coordinate-level overlap between eQTLs and MPRA identified 269 eGenes, covering 80 loci.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several examples were discussed in a perspective article on TWAS [6]. Colocalization analysis has a similar problem ; for example, in a Schizophrenia study, 282 genes in 78 risk loci, showed evidence of colocalization [16]. Secondly, at a biochemical level, co-regulation of genes by the same regulatory elements is common [17].…”
Section: Introductionmentioning
confidence: 99%